Pengaruh social media promotion dan electronic word of mouth terhadap keputusan pemilihan pada perguruan tinggi - Azmar Azmar; Patria Laksamana (Sekolah Pascasarjana Perbanas Jakarta, 2018)
Along with the internet growth and its evolution, electronic Word of Mouth (eWOM) has become an important phenomenon in decision making. The purpose of this study is to analyze the effect of social media promotion and eWOM on the official accounts of social media of Perbanas Institute on higher-education selection decision by prospective students. This study uses a quantitative approach. The sample of this study were 179 respondens who are taken by using purposive sampling technique and who have interacted with the official accounts of social media of Perbanas Institute both at Perbanas Institute Jakarta campus and Bekasi campus. The research instrument uses questionnaire and analyzed using multiple regression. The result of this research shows that the independent variables of personal relevance, interactivity, message, and brand familiarity have positive and significant effect on eWOM. Then eWOM has positive and significant effect on the Purchase Decision. And simultaneously personal relevance, interactivity, message, and brand familiarity (Social Media Promotion) have a positive and significant effect on Purchase Decision. In theoritical perspective, this study has a significant contribution in broadening the study of mobile marketing. Whereas for managerial perspective, is can offer more efective strategies and recomendations for expand the customer base. Limitations and future direction are also discussed. Keywords: Personal Relevance, Interactivity, Message, Brand Familiarity, Electronic Word of Mouth, Social Media Promotion, Purchase Decision